2022
DOI: 10.1039/d2an00721e
|View full text |Cite
|
Sign up to set email alerts
|

Fabric-based in situ synthesis of gold nanoparticles for continuous enhanced heterogeneous chemiluminescence online detection of carbon dioxide

Abstract: A novel method to achieve real-time and long-term continuous measurement of CO2 based on in situ synthesis of AuNPs on fabrics is reported. A heterogeneous CO2 detection method and the application of continuous catalytic chemiluminescence immobilized by nanoparticles were also developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Therefore, Chen Qi found that AuNPs can sensitize the CO 2 -H 2 O 2 -KOH chemiluminescence system and loaded AuNPs on nylon fabrics for online detection of CO 2 to solve problems such as precious metal waste. 9 Compared with traditional fabrics, electrospun nano-ber membranes (NMs) are more appropriate loading bases for sensitizer materials because of their higher porosity and specic surface area. 10 In recent years, articial or natural polymers have been used as raw materials to produce nano-ber membranes (NMs) by electrospinning technology.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Chen Qi found that AuNPs can sensitize the CO 2 -H 2 O 2 -KOH chemiluminescence system and loaded AuNPs on nylon fabrics for online detection of CO 2 to solve problems such as precious metal waste. 9 Compared with traditional fabrics, electrospun nano-ber membranes (NMs) are more appropriate loading bases for sensitizer materials because of their higher porosity and specic surface area. 10 In recent years, articial or natural polymers have been used as raw materials to produce nano-ber membranes (NMs) by electrospinning technology.…”
Section: Introductionmentioning
confidence: 99%